Macroeconomics - Baumol, William J. (Thomson/South-Western, 2006)
This microeconomics text is well known for using the Keynesian model in the teaching of economics; yet in recent editions, the authors have expanded coverage of the growth model considerably to achieve more balanced coverage. The text uses the aggregate supply/ aggregate demand model as a fundamental tool for learning macroeconomics. It achieves the right level of rigor and detail, presenting complicated concepts in a relatively straightforward manner and using timely economic data. Using puzzles, issues, and well-developed examples, the authors provide a good balance of theory to application. Homework Xpress and Aplia are available with the Anniversary Tenth Edition and two new sets of end of chapter questions have been added as well to help students prepare for exams: "Test Yourself" and "Discussion Questions"